Respuesta :

First, we should figure out an equation and take note that we are dealing with complementary angles (angles that add up to 90 degrees)

Your equation:
(2x + 1) + (x - 7) = 90

Now solve!
====================================================================
SOLVING...

(2x + 1) + (x - 7) = 90

Simplify and combine like terms
2x + 1 + x −7 = 90
2x + 1 + x + −7 90
(2x + x) (1 + −7) 90
3x + −6 90

Add 6 to each side
3x − 6 + 6 90 6
3x = 96

Divide each side by 3
3x ÷ 3 = 96 ÷ 3
x = 32

ACCESS MORE